1976
DOI: 10.1002/bip.1976.360151209
|View full text |Cite
|
Sign up to set email alerts
|

Study of thermal denaturation of lysozyme and other globular proteins by light‐scattering spectroscopy

Abstract: SynopsisThe technique of intensity correlation light-scattering spectroscopy has been used to accurately determine the extent of physical swelling of lysozyme, ribonuclease, and chymotrypsinogen produced by thermal denaturation. The change in hydrodynamic radius is deduced from direct measurements of the diffusion coefficient, carried out in the temperature range 20' to 70°C a t various values of pH in the range 1.0 to 3.0 a t ionic strengths of from 0.01 M to 0.2 M . An average radius increase of 18% is obser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
53
0

Year Published

1987
1987
2012
2012

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(64 citation statements)
references
References 35 publications
9
53
0
Order By: Relevance
“…It follows from our measurements that for lysozyme in aqueous solution with zero concentration of ethanol the value of the hydrodynamic radius equals (1.856 ± 0.023) nm, which is in a good agreement with the results known from literature (e.g. 1.811 nm [22], 1.85 nm [25], 1.87 nm [24], 1.96 nm [27]). When the ethanol concentration reaches 9.91% (v/v), hydrodynamic radius increases up to (2.277 ± 0.020) nm.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…It follows from our measurements that for lysozyme in aqueous solution with zero concentration of ethanol the value of the hydrodynamic radius equals (1.856 ± 0.023) nm, which is in a good agreement with the results known from literature (e.g. 1.811 nm [22], 1.85 nm [25], 1.87 nm [24], 1.96 nm [27]). When the ethanol concentration reaches 9.91% (v/v), hydrodynamic radius increases up to (2.277 ± 0.020) nm.…”
Section: Resultssupporting
confidence: 92%
“…The change of the B 22 value is independent of NaCl concentration, which means that presence of ethanol molecules does not aect electrostatic proteinprotein interaction. Changes of the diusion coecient, presented above, could be attributed to the increasing viscosity of the solvent, as it was in the waterglycerol solutions [24] or to the denaturation process, as it was observed in the case of temperature denaturation [25] and chemical denaturation by guanidine hydrochloride (Gdn · HCl) [26]. Since the viscosity of waterethanol solution changes from 1.05 × 10 (for 10.6% EtOH (v/v)) [16], we assume that the observed changes are connected with the structural transformations of the protein molecule related to its dehydration.…”
Section: Resultsmentioning
confidence: 80%
See 1 more Smart Citation
“…42 The overall repulsive character of the protein-protein interactions and the low lysozyme concentrations, C LYS < 10 g L -1 , explain why The self-diffusion coefficient, D 0 , was calculated from literature values of the hydrodynamic radius, R h of (0) the native protein for 0 e DMSO e 1 and of (O) the native protein for 0 e DMSO e 0.6 (R h ) 1.87) and the denatured protein for 0.7 e DMSO e 1.0 (R h ∼ 2.75). 37,41,43 54. We assume that lysozyme has 193 exchangeable protons in the folded states and 263 exchangeable protons in the unfolded states.…”
Section: Resultsmentioning
confidence: 99%
“…Nicoli and Benedek [38] found that the heat denaturation of lysozyme increases the hydrodynamic radius from 1.85 nm to 2.18 nm and not to the 4.9 nm calculated for a random coil. Our results for sepia cartilage collagen suggest that hydrodynamic volume (rather hydrodynamic radius) increases with the increase in temperature below the denaturation temperature of collagen.…”
Section: Hydrated Volume and Interaction Of Surfactant With Collagenmentioning
confidence: 96%